Академічна культура в науці та освіті: причини академічної недоброчесності - Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Boltianska, Natalia; Болтянський, Олег Володимирович; Болтянский, Олег Владимирович; Boltianskyi, Oleh; Подашевська, О. І.; Серебрякова, Н. Г.; Субочев, О. І. (ТДАТУ, 2021)
UA : В статті розглядається питання академічної культури в науці та освіті, а саме висвітлюються причини академічної недоброчесності. EN : The article considers the issue of academic culture in science and education, namely the causes of academic dishonesty.
Academic culture in science and education: causes of academic unfairness
Keywords: академічна культура; доброчесність; здобувачі вищої освіти; заклади вищої освіти; причини; academic culture; integrity; applicants for higher education; institutions of higher education; reasons